Theoretical and experimental study on multi-phase model of thermal conductivity for fiber reinforced concrete. (1st September 2017) - Liu, Kai; Lu, Lin; Wang, Fang; Liang, Wei
Highlights: Steel fiber and carbon fiber were used to make fiber reinforced concrete with different mix proportions. Effects of different experimental parameters on thermal conductivity of FRC were investigated. FRC must be regarded as a three-phase composite material for calculating the thermal conductivity. Multi-phase theoretical model was derived based on the composite material theory. Multi-phase prediction model between thermal conductivity and fiber volume fraction was proposed. Abstract: In order to clarify the influence of fiber volume fraction on the thermal properties of cement concrete, and improve the calculated accuracy, thermal conductivities of steel fiber reinforced concrete (SFRC) and carbon fiber reinforced concrete (CFRC) were researched through experiments (the QTM-300 or the LFA457) and the composite theory's models. The influence of fiber volume fraction and the water-cement (W/C) ratio on thermal conductivities of SFRC and CFRC was investigated. Afterwards, the thermal conductivities of fiber reinforced concrete (FRC) were calculated respectively via two-phase theoretical models, multi-phase theoretical models which were derived by composite material theory, and multi-phase prediction model which was proposed based on the different composition materials' thermal conductivity (cement mortar, aggregate, different fiber) and their volume fraction. Additionally, the above three models were compared and verified by experimental results respectively. The results show that although the volume fraction of the fibers in the concrete is the smallest, the FRC should be still seen as three-phase composite materials. Therefore, the thermal conductivity of FRC will be better predicted by both of the three-phase serial-parallel model and multi-phase prediction model, and the calculated results of the prediction model are closer to experimental results.